МОРФОЛОГИЯ, ГЕНЕЗИС И РЕСУРСНЫЕ ПЕРСПЕКТИВЫ ОТРАБОТАННЫХ РОССЫПЕЙ ДАЛЬНЕГО ВОСТОКА - Мирзеханов Г.С.; Мирзеханова З.Г. (My University, 2005)
The investigation of refuse piles of more then 40 gold placers at different stages of mining is carried out. The morphologic and morphometric features of piles are described as well as their dependence on mining technology. The resources of piles for subsequent exploitation (their gold content) were evaluated.
Keywords: 551.438(571.6)